Non-coding RNAs in Cardiac Intercellular Communication - Videira, Raquel Figuinha; da Costa Martins, Paula A. (Frontiers in Physiology, 2020)
Intercellular communication allows for molecular information to be transferred from cell to cell, in order to maintain tissue or organ homeostasis. Alteration in the process due to changes, either on the vehicle or the cargo information, may contribute to pathological events, such as cardiac pathological remodeling. Extracellular vesicles (EVs), namely exosomes, are double-layer vesicles secreted by cells to mediate intercellular communication, both locally and systemically. EVs can carry different types of cargo, including non-coding RNAs (ncRNAs), which, are major regulators of physiological and pathological processes. ncRNAs transported in EVs are functionally active and trigger a cascade of processes in the recipient cells. Upon cardiac injury, exosomal ncRNAs can derive from and target different cardiac cell types to initiate cellular and molecular remodeling events such as hypertrophic growth, cardiac fibrosis, endothelial dysfunction, and inflammation, all contributing to cardiac dysfunction and, eventually, heart failure. Exosomal ncRNAs are currently accepted as crucial players in the process of cardiac pathological remodeling and alterations in their presence profile in EVs may attenuate cardiac dysfunction, suggesting that exosomal ncRNAs are potential new therapeutic targets. Here, we review the current research on the role of ncRNAs in intercellular communication, in the context of cardiac pathological remodeling.